Restaurant Tax Audit Analysis in the Order to Test Taxpayer Compliance at Suku Badan Pendapatan Daerah Kota Administrasi Jakarta Selatan in 2021 - Alief Ramdan; Tuaraja Simon Sinaga (Yayasan Ilomata, 2022)
Based on temporary research, there are still many taxpayers who are not obedient in fulfilling their taxes, such as paying taxes not on time and not by the amount of tax owed. This study aims to find out and analyze the Restaurant Tax Audit Analysis in the Framework of Testing Taxpayer Compliance at the South Jakarta City Administration Regional Revenue Tribe in 2021. The research method used in this study is a qualitative descriptive method. The criteria for the sources that the author uses as informants (parties/interviewees) in this study are those who control and understand the conditions of the research object, who are involved or occupy positions related to the topic under study, and have sufficient time to be interviewed. Restaurant Tax Audit in the Context of Testing Taxpayer Compliance at the Regional Revenue Sub-District of the City of South Jakarta Administration has been carried out well, especially from the audit procedures and audit results, but the ability of the tax authorities still needs to be improved.